PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Agustin, Dinda Nurfiqi; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The value of the company can provide maximum shareholder prosperity if the company's share price increases. The higher the stock price in a company, the income and prosperity of investors will also increase and have a good impact on increasing the value of the company. This research is a causality research. The population in this study are pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that profitability has a significant positive effect on dividend policy, profitability has a negative and insignificant effect on firm value, dividend policy has a negative but significant effect on firm value. The results of the indirect effect hypothesis test show that the profitability variable on firm value through dividend policy has a negative and insignificant effect.